The Camareta cave: a reassessment of its Palaeohispanic inscriptions (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper provides the results of a thorough, comprehensive reexamination of the Palaeohispanic inscriptions of the Camareta cave (Hellín, Albacete). The authors conclude that there is only one inscription, which consist of two lines and is written in the Southern Iberian script, and they provide a palaeographic and linguistic analysis of the inscription
Keywords: Palaeohispanic inscriptions; Iberian language; Iberian script; Rock inscriptions